SYSTEMATIC LITERATUR REVIEW: EKSPLORASI ETNOMATEMATIKA PADA PERMAINAN TRADISIONAL - Oktavia, Thessa; Deswita, Ria; Seprina Anggraini, Reri (MEGA: Jurnal Pendidikan Matematika, 2024)
In recent decades, attention to the preservation of local culture, especially in the context of education, has increased. This research explores ethnomathematics as a bridge between culture and mathematical concepts through traditional games. Ethnomathematics not only functions to understand mathematical concepts in a cultural context, but also to preserve traditions. The method used is a systematic literature study with qualitative analysis of 9 articles published between 2018 and 2024. The findings show that traditional games, such as marbles, congklak, and engklek, contain various mathematical concepts, including geometry, calculation, and logic. The results of this research provide new insights for educators about the importance of cultural context in mathematics learning, and encourage the development of a more inclusive curriculum. In addition, this research contributes to preserving local culture and increasing students' understanding of mathematics. By integrating traditional games in education, it is hoped that mathematics learning will become more interesting and relevant for students.